1993
DOI: 10.1042/bj2910263
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic AMP enhances agonist-induced Ca2+ entry into endothelial cells by activation of potassium channels and membrane hyperpolarization

Abstract: The mechanism underlying cyclic AMP (cAMP)-mediated amplification of agonist-induced Ca2+ responses in endothelial cells was investigated in pig endothelial cells. Forskolin, adenosine and isoprenaline, as well as the membrane-permeant cAMP analogue dibutyryl cAMP, enhanced bradykinin-induced rises in intracellular free Ca2+ as well as bradykinin-induced Mn2+ entry. These agents were also found to hyperpolarize endothelial cells without increasing intracellular Ca2+ by itself, i.e. in the absence of bradykinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
33
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 28 publications
7
33
0
Order By: Relevance
“…Similarly, Sturek et al (1991) reported a half-reduction of the bradykinin peak response in the absence of extracellular Ca2+. The bradykinininduced Ca2+ response also became transient in the absence of external Ca+, as shown by a 52% reduction in the and 132-0 + 43-9 s (n = 10) with extracellular Ca2P, compared with 26-1 + 3-9 mV (n = 9) and 40 0 + 3 0 s (n = 9) in the absence of extracellular Ca2P (P < 0 05 Confirming our observations in coronary artery endothelial cells, the BKCa channel is less frequently observed than are endothelial cation channels: it accounts for 2 % of the patches in endocardial endothelial cells and 4% of the patches in aortic endothelial cells (Graier, Kukovetz & Groschner, 1993;Manabe, Ito, Matsuda, Noma & Shibata, 1995). Based upon its conductance, however, this channel could nevertheless play a major physiological role.…”
supporting
confidence: 73%
“…Similarly, Sturek et al (1991) reported a half-reduction of the bradykinin peak response in the absence of extracellular Ca2+. The bradykinininduced Ca2+ response also became transient in the absence of external Ca+, as shown by a 52% reduction in the and 132-0 + 43-9 s (n = 10) with extracellular Ca2P, compared with 26-1 + 3-9 mV (n = 9) and 40 0 + 3 0 s (n = 9) in the absence of extracellular Ca2P (P < 0 05 Confirming our observations in coronary artery endothelial cells, the BKCa channel is less frequently observed than are endothelial cation channels: it accounts for 2 % of the patches in endocardial endothelial cells and 4% of the patches in aortic endothelial cells (Graier, Kukovetz & Groschner, 1993;Manabe, Ito, Matsuda, Noma & Shibata, 1995). Based upon its conductance, however, this channel could nevertheless play a major physiological role.…”
supporting
confidence: 73%
“…In corneal endothelial cells, CCE was inhibited by the K ϩ channel blocker tetrabutylammonium 3 and high [K ϩ ] depolarization. 4 Although hyperpolarization itself could not increase [Ca 2ϩ ] i in vascular endothelial cells (74) and corneal endothelial cells, 3 we speculate that cytochrome P-450 metabolites may additionally enhance CCE by hyperpolarizing the cell membrane through activating K ϩ channels. store depletion causes AA release and activates cytochrome P-450s in the ER membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the adenylyl cyclase inhibitor 2Ј,5Ј-DDA, which has previously been shown to abolish EDHF-type relaxations and cAMP accumulation in rabbit iliac arteries (11,12), abolished subintimal smooth muscle potential changes evoked by ACh. Although cAMP could theoretically hyperpolarize endothelial and smooth muscle cells by activating K ϩ channels directly (31,32), this action is unlikely to contribute significantly to the EDHF phenomenon in rabbit arteries as IBMX hyperpolarized, and 2Ј,5Ј-DDA depolarized, subintimal muscle cells by Ͻ5 mV in strips with intact endothelium. Furthermore, IBMX did not affect smooth muscle membrane potential in endotheliumdenuded preparations, despite causing sustained 2-fold increases in cAMP levels.…”
Section: Discussionmentioning
confidence: 99%